All that's frozen melts into air: Arctic cinemas at the end of the world. (1st December 2013) - MacKenzie, Scott; Stenport, Anna Westerståhl
Drawing on the concepts of the sublime and the spectacle, this article examines the ways in which global cinemas have often mobilized the trope of the Arctic as the end of the world. Drawing on a radically disparate set of films, including examples from Swedish and Danish art cinema; Cold War documentaries made or supported by the Danish and American governments for both general release and television; 1950s 'True Life Adventures' nature documentaries made by the Disney studio; Creation, a work by American avant-garde film-maker Stan Brakhage; and To the Arctic, a recent IMAX 3D film. We argue that most of these works eradicate the material, cultural and geographical specificity of the Arctic for political and ideological reasons.